Biomimetic Catechol-Incorporated Polyacrylonitrile Nanofiber Scaffolds for Tissue Engineering of Functional Salivary Glands - Kwon, Seokjun; Ryu, Ji Hyun; Kim, Junchul; Shin, Hyun Ho; Chung, Gehoon; Taghizadeh, Ali; Lee, Jung-Hwan; Kim, Jongho; Ku, Bon-Cheol; Park, Kyungpyo; Lee, Sang-woo (The Korean Society for Biomaterials | BioMed Central, 2025)
Replacing damaged salivary glands with in vitro-generated artificial glands offers a fundamental solution for salivary gland dysfunction. However, this approach remains challenging due to the gland's complex structure and cellular heterogeneity. Since natural organogenesis of salivary glands successfully orchestrates these complex processes, replicating the developmental niche in vitro is considered a promising solution. However, it consists of complex, branched structures formed by multiple factors; thus, recapitulation of these factors in vitro using a single type of biomaterial is difficult to achieve. Therefore, this study aims to design a scaffold capable of spontaneously mimicking salivary gland's developmental niche. Herein, we demonstrate that catechol-incorporated polyacrylonitrile (PAN-C) nanofiber scaffold spontaneously transforms into biomimetic structures by adsorbing embryonic mesenchyme-derived extracellular matrix (ECM) and growth factors. Accumulated adsorption of ECM and growth factors on PAN-C nanofibers promoted the proliferation, morphogenesis, and functional differentiation of embryonic salivary gland (eSG) organoids in vitro. Transcriptome analysis revealed that the PAN-C nanofiber scaffold effectively reduced mechanical stress-induced gene expression while promoting proliferation and differentiation of salivary gland epithelial cells. In eSG organoids cultured on PAN-C nanofiber scaffolds, the proportion of functional acinar cells expressing apically localized aquaporin-5 was substantially higher than those cultured on polycarbonate membranes, a conventional culture material. Therefore, PAN-C nanofiber scaffolds provide an effective and economical method for generating functional eSG organoids in vitro.